TANGGUNG JAWAB NOTARIS DALAM PEMBUATAN PERJANJIAN PENGIKATAN JUAL BELI (PPJB) GANDA (STUDI KASUS NOTARIS NKA DI KOTA DENPASAR) - , Odilia Chrisanta B ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The entitled research âThe Liability of Notary in Making the Agreement of Dual Sale and Purchase Binding (Case Study of Notary in Denpasar City)âaims to know the legal process that may be taken by the buyer as an incapacitated party of the agreement of dual sale and purchase binding made by the notary and to know the liability of the notary toward one of the buyers as the incapacitated party of the agreement of dual sale and purchase binding. This research was a juridical empiric research with the legal research of the primary data and secondary data. The entire collected data were analyzed through qualitative method. The result of this research showed that the first agreement of dual sale and purchase binding was valid, and the second invalid agreement of dual sale and purchase binding represented a simulation of the agreement of dual sale and purchase binding that against the law, so that the aforementioned deed was null and void. As in private matter, the notary acted against the law, so was determined that the notary should joint liability with the defendant 1 to pay back the second incapacitated buyer. As in criminal matter, the dispute still could not be continued to the investigation yet due to lack of evidences and the submission flawed of fraud and embezzlement articles in the case of the agreement of dual sale and purchase binding. The plaintiff resubmitted the statement on the basis of the article 16 of Notary Occupation Law, representing that the notarial deed shall express the truth and article 266 jo 55 Indonesian Criminal Code where the notary jointly insert false statements in the deed.